OpenStudy (anonymous):

Solve the following system of equations. 2x – 3y + z = –1 3x + 2y + 2z = –1 x – y – 3z = –4

5 years ago
OpenStudy (anonymous):

Multiply third equation by 2 and tell what you get..

5 years ago
OpenStudy (anonymous):

I multiplied it by -2 and got y+8z=-7

5 years ago
OpenStudy (anonymous):

You, multiply (-2) with third equation?? Show me your full work I think there is a mistake in that..

5 years ago
OpenStudy (anonymous):

|dw:1340816375750:dw|

5 years ago
OpenStudy (anonymous):

It will be -y -3y + 2y = -y

5 years ago